PENGARUH PERUBAHAN DIMENSI TERHADAP NILAI ISOLASI PADA BRANCH LINE COUPLER - Yudi Barnadi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The extent of national waters is a challenge for the government in efforts to secure marine areas from unlawful acts. Indonesia needs to really monitor the most vulnerable areas so that the national fish resources can be enjoyed by the community. To do this, bases for surveillance ships (KKP, Bakamla, TNI AL) need to be built in the area. One of the efforts that need to be done is to increase strict government supervision by increasing security as well as developing appropriate rules in order to prevent violations of the law. the ability of the Navy and the National Police to guard the entire sea area, they must use coastal surveillance radar. This pulse radar has electromagnetic waves that are disconnected rhythmically, and has only one antenna that is used to transmit and receive signals. To send and receive signals, these radars need a splitter called a duplexer. The duplexer serves to isolate the transmitted signal and the received signal and the main component of the duplexer is the Branch-Line Hybrid Coupler. Couplers have parameters that indicate performance such as: Return Loss, Power Coupling, Insertion Loss and insulation value. In this study, a study was conducted to determine the effect of dimensional changes on the insulation value of the Branch line coupler. Isolation is very important because it affects the performance of the duplexer. The smaller the value the better the performance of the duplexer. This research was conducted by modifying the length and width of the impedance Coupler line. Branch-Line Coupler designed. in the form of microstrips and fabricated using FR-4 substrate which has a dielectric constant of 4.6, a thickness of 1.3 mm, and an operating frequency of 3 GHz. To get the optimal value for isolation characteristics, the impedance channel must be modified, namely the length and width of the arm series (Z0 = 50 ), the length and width of the arm series (Z0 = 35.35 ), and the length and width of the shunt arm (Z0 = 50 ). The isolation optimization result is -67,786 dB.